Pharmacological preconditioning protects from ischemia/reperfusion‐induced apoptosis by modulating Bcl‐xL expression through a ROS‐dependent mechanism. (4th January 2021) - Rozier, Romain; Paul, Rachel; Madji Hounoum, Blandine; Villa, Elodie; Mhaidly, Rana; Chiche, Johanna; Verhoeyen, Els; Marchetti, Sandrine; Vandenberghe, Ashaina; Raucoules, Marc; Carles, Michel; Ricci, Jean‐Ehrland
Abstract : Myocardial ischemia/reperfusion (I/R) injury is a frequent perioperative threat, with numerous strategies developed to limit and/or prevent it. One interesting axis of research is the anesthetic preconditioning (APc) agent's hypothesis (such as sevoflurane, SEV). However, APc's mode of action is still poorly understood and volatile anesthetics used as preconditioning agents are often not well suited in clinical practice. Here, in vitro using H9C2 cells lines (in myeloblast state or differentiated toward cardiomyocytes) and in vivo in mice, we identified that SEV‐induced APc is mediated by a mild induction of reactive oxygen species (ROS) that activates Akt and induces the expression of the anti‐apoptotic protein B‐cell lymphoma‐extra large (Bcl‐xL), therefore protecting cardiomyocytes from I/R‐induced death. Furthermore, we extended these results to human cardiomyocytes (derived from induced pluripotent stem ‐ IPS ‐ cells). Importantly, we demonstrated that this protective signaling pathway induced by SEV could be stimulated using the antidiabetic agent metformin (MET), suggesting the preconditioning properties of MET. Altogether, our study identified a signaling pathway allowing APc of cardiac injuries as well as a rational for the use of MET as a pharmacological preconditioning agent to prevent I/R injuries. Abstract : Myocardial ischemia/reperfusion (I/R) injury contributes to patient condition's worsening in numerous clinical settings. Preconditioning interventions are developed to reduce myocardial suffering. Here, Rozier and coll . demonstrated in cell lines, in iPS‐derived human cardiomyocytes, and in mice that the anesthetic agent sevoflurane can protect cells from I/R‐induced injuries. They also demonstrated that metformin can protect cardiomyocytes through the same signaling pathway involving ROS‐dependent activation of Akt resulting in B‐cell lymphoma‐extra large (Bcl‐xL)‐increased expression.